Ol' Max Evans : the first thousand years - Randles, Slim. frey50 (Albuquerque : University of New Mexico Press, 2004)
Max Evans is a Southwester treasure. his talent as a story-teller has brought the American West to life for countless readers and has reached even more people around the world on the motion picture screen. Now Slim Randles captures the essence of Ol' Max in this fascinating biography - a feat somewhat akin to capturing lightning in a bottle. Great reading about a grand man!
A biography.
Keywords: Evans, Max, -- 1925-; Authors, American -- 20th century; New Mexico -- Intellectual life -- 20th century; New Mexico -- In literature; New Mexico